ALMA observations of the Orion Integral Filament: evidence for fibers in a massive cloud. Issue Volume 14:Issue S345(2019) (August 2018) - Hacar, Alvaro; Tafalla, Mario; Forbrich, Jan; Grossschedl, Josefa
Abstract: The connection between low- and high-mass filaments is a matter of strong debate. In order to bridge these two filamentary regimes, we have investigated the internal structure of the Integral Filament in Orion using ALMA observations of the N2 H + (1-0) emission line in Band 3 in combination with previous single-dish data. Our ALMA mosaics, the largest of its kind carried out so-far in local clouds, reveal the presence of multiple sonic-like fibers inside this massive filament. In combination with the identification of fibers in regions such as Taurus, Musca, and Perseus, the first unambiguous detection of fibers in Orion highlights the importance of these gas substructures as the fundamental building blocks of both low- and high-mass filaments.